2005
DOI: 10.1364/opex.13.000918
|View full text |Cite
|
Sign up to set email alerts
|

Equilateral hyperbolic moir� zone plates with variable focus obtained by rotations

Abstract: We present equilateral hyperbolic zone plates with variable focal length, which are formed as moiré patterns by a mutual rotation of two identical basic grids. Among others, all principal zone plates, except of the spherical one, can be used as these basic transmittances. Three most important advantages of the proposed moiré zone plates are: a constant aperture of the created element during the mutual movement of basic grids, lack of aberrations due to their undesired mutual lateral displacements and high diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Also four small lobes at the diagonals are observed. The cross-like pattern has been observed previously [8], [9], [10], [11].…”
Section: Numerical Simulation Of the Focusing Capabilities Of Square supporting
confidence: 80%
See 1 more Smart Citation
“…Also four small lobes at the diagonals are observed. The cross-like pattern has been observed previously [8], [9], [10], [11].…”
Section: Numerical Simulation Of the Focusing Capabilities Of Square supporting
confidence: 80%
“…In some designs, circular symmetry is not used, as those based on hyperbolic contours or shapes. These designs show interesting properties and allow new uses [8][9] [10]. Also a square FZP has been proposed as a combination of cylindrical FZP [11].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, researchers have proposed the Moiré effect [24,25] combined with diffractive optical elements (DOEs) to realize zooming by relatively rotating two DOEs [26,27]. In this paper, we further verify that the Moiré effect can be realized by the combination of two chiral GEMSs and they can be used to form a continuous-zoom metalens.…”
Section: Introductionmentioning
confidence: 55%
“…[ 147,148 ] A derivative of the Alvarez system is also presented where the two lenses are coaxially rotated rather than being parallelly moved, which is inspired by the Moiré lens. [ 149–153 ] Cui et al. [ 151 ] proposed a rotationally tunable polarization‐dependent varifocal metasurface, and Yilmaz et al.…”
Section: Functionalitiesmentioning
confidence: 99%
“…[147,148] A derivative of the Alvarez system is also presented where the two lenses are coaxially rotated rather than being parallelly moved, which is inspired by the Moiré lens. [149][150][151][152][153] Cui et al [151] proposed a rotationally tunable polarization-dependent varifocal metasurface, and Yilmaz et al [152] demonstrated a polarizationindependent varifocal metasurface. Subsequently, Guo et al [153] fabricated a 3.5× continuous varifocal meta-lens in the microwave band, with an improved N.A.…”
Section: External Tunabilitymentioning
confidence: 99%